Micronutrient Fortification of Pearl Millet [Pennisetum glaucum (L.) R. Br.] Hybrids using Customized Fertilizer Formulation - Kumar, Manoj; Singh, Ummed; Raiger, P. R.; Singh, L. Netajit; Parewa, H. P.; Chouhan, Rekha (International Journal of Bio-resource and Stress Management, 2021)
The studies were undertaken at ICAR-AICRP on Pearl Millet, Research Farm, ARS, Mandor, Jodhpur (Agriculture University, Jodhpur), Rajasthan, India during July to October of both the 2019 and 2020. The experiment was consisted of three fertilizers (Control, Nutrient supply through straight fertilizers and Nutrient supply through customized fertilizer) and seven pearl millet hybrids (‘MPMH 21’, ‘MPMH 17’, ‘RHB 177’, ‘RHB 173’, ‘HHB 67 (Improved)’, ‘HHB 197’ and ‘HHB 272’) in FRBD and replicated thrice. Findings revealed, application of customized fertilizer of the grade 6:6:2:1 (N:P2O5:K2O:Zn) to pearl millet substantially enhanced Zn concentration in the roots, shoots, and leaves at panicle initiation (47.30, 54.31, 52.33 mg kg-1), 50% flowering (40.30, 50.96, 50.10 mg kg-1) and at harvest (45.27, 46.54, 47.29 mg kg-1), respectively, over control. Similarly, Fe concentration in the roots, shoots and leaves were also increased markedly due to the application of customized fertilizer. Substantially higher Zn (56.42 mg kg-1), Fe (39.50 mg kg-1), Mn (15.13 mg kg-1) and Cu (18.31 mg kg-1) concentrations in the pearl millet grain was also fetched by applying customized fertilizer. Moreover, customized fertilizer application statistically enhanced grain (2,010 kg) and straw (3,417 kg) yields over control. Among pearl millet hybrids, ‘HHB 67 Improved’ recorded substantially higher Zn (61.97 mg kg-1), Fe (43.98 mg kg-1) and Mn (15.46 mg kg-1) concentration in grain and Cu (25.09 mg kg-1) concentration in straw. Albeit, ‘HHB 173’ noticed significantly higher Cu (19.60 mg kg-1) concentration in grain. Further, among hybrids, ‘MPMH 17’ out yielded (1,958 kg ha-1) followed by ‘RHB 173’ (1,795 kg ha-1).